Longing to Belong in One’s Own Homeland: Tracing the Topophilic Cartography in Anita Sethi’s I Belong Here: A Journey Along the Backbone of Britain - Dalal, Sanghamitra (Text Matters: A Journal of Literature, Theory and Culture, 2024)
In this article I will read I Belong Here: A Journey Along the Backbone of Britain (2021) by Anita Sethi, the Manchester-born woman of colour, to explore how journeying through natural landscapes can be perceived as an emblematic reclamation of one’s home and belonging. A victim of a race-hate crime that questioned her right to belong in her country of birth on account of her race, while she was on her way from Liverpool to Newcastle on the TransPennine Express train in 2019, Sethi resolves to undertake this journey on foot across the Pennines, a range of uplands in the northern England—known as the “backbone of Britain” and designated “Areas of Outstanding Natural Beauty”—in order to reclaim her right to belong and roam freely in the land which she longs to call home. As her physical act of walking amidst intense beauty is intertwined with her internal journey of growing up as a brown woman in a predominantly white Britain, the narrative traverses beyond the Pennines, and is transformed into a testimony of how nature salves wounded souls in a fractured world, subjects who are strangely interconnected by myriad cultures and identities, movements and migrations. Consequently, drawing from the idea of topophilia, proposed by Gaston Bachelard and popularized by Yi-Fu Tuan, I will argue that Sethi’s memoir eventually transcends the disturbing reality of being the estranged Other and charts a topophilic cartography to shepherd the alienated and the unhomed toward a sense of home and belonging.